Functional diversity of soil microbiomes in forest ecosystems and the spread of ESKAPE pathogens - Lyudmyla Symochko; Olena Demyanyuk; M.N. Coelho Pinheiro (EQA)
The article presents original research results focused on the long-term investigation of the soil microbiome in forest ecosystems, particularly examining microbial community structure, the abundance of major ecological-functional groups, and the spread of ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter species). The study aims to analyze the impacts of both endogenous and exogenous factors on soil microbial communities and succession processes. Monitoring of soil microbiome in the forest ecosystems of the Carpathian Biosphere Reserve showed changes in microbial communities over a 12-year period. These changes included an increase in the number of spore-forming, pedotrophic and oligotrophic bacteria. Furthermore, an increased presence of ESKAPE pathogens in the soil was observed. The Antibiotic Resistance Profile (ARP) of ESKAPE pathogens in unmodified forest ecosystems was determined for the first time. Long-term studies investigating changes in soil microbial communities in natural ecosystems revealed that the soil microbiome in such environments is impacted by external factors and can act as a reservoir for pathogenic bacteria, posing risks to both human and ecosystem health.